Multiscale Modeling and Simulation of Nano‐Carriers Delivery through Biological Barriers—A Review. Issue 1 (23rd October 2018) - Shi, Xinghua; Tian, Falin
Abstract: The past several decades have witnessed the explosion of nanomedicine for cancer therapy, where notable research efforts have been made in synthesizing and delivering nano‐carriers (NCs) to specific tumor sites. The effective treatment of cancer with nanomedicine poses the requirements of high solubility, prolonged circulation, low toxicity, strong targeting ability, specific distribution, and high tissue penetration capability of NCs, involving interdisciplinary research and posing challenges to the community. Along with experimental contributions for the development and application of NCs to treat cancer, multiscale modeling and simulation have also made considerable contributions to the understanding of the synthesis, translocation, and delivery of NCs and their payloads. Here, recent advances of modeling and simulation work are selected to elucidate some key concepts, methods, and applications of NCs during synthesis and drug delivery, such as assembly, translocation, targeting, cellular uptake, and penetration in tissue. The advantages and limitations of each method are highlighted, and the future perspectives in this field are also discussed. Abstract : Understanding how nanoparticles (NPs) interact with cellular systems becomes crucial for the future development of safe and efficient delivery NPs with designed functions. Here, the detailed information and mechanisms of the general nature of NPs–cell interaction based on recent simulation results are summarized. Moreover, fundamental questions that should be addressed in the computer simulation area in future research are highlighted.